Kritische Theologie: Paul Tillich in Frankfurt (1929-1933) - Schreiber, Gerhard; Schulz, Heiko (Tillich research, 2015)
This volume examines the multifaceted origins of Paul Tillich’s “critical theology” during the Frankfurt years (1929–1933) from the perspectives of source and reception history. In this way, it provides a compelling picture of the rich interactions between Tillich and his academic environment as well as the spiritual situation at the University of Frankfurt just before the National Socialist takeover.